A development of an advanced shift control algorithm for a hybrid vehicles with automated manual transmission. (29th October 2004) - Jo, Han-Sang; Park, Yeong-Il; Lee, Jang-Moo; Lee, Hyeoun-Dong, Seung-Ki Sul
In this study, an advanced shift control algorithm for a parallel hybrid drivetrain system with automated manual transmission (AMT) is proposed. The AMT can be easily realised by mounting pneumatic actuators and sensors on the clutch and on the shift levers of the conventional manual transmission (MT). By using the electronic-controlled AMT, the engine load and the induction machine, it is possible to achieve the integrated control of the overall system regarding the efficiency and the performance of the vehicle. Performing the speed control of the induction machine and the engine, the synchronisation at gear shifting and the smooth engagement of the clutch are guaranteed. It also enables the shift shock to be reduced and the shift time to be shortened. Hence, the shift quality and the driving comfort of the vehicle are improved. Various dynamometer-based experiments are carried out to prove the validity of the proposed shift control algorithm.